Effects of relaxation training after volleyball exercise on blood lactate concentration, muscle hardness, and heart rate - Bian, Yonghong (Frontiers in Physiology, 2025)
BackgroundVolleyball recovery optimisation is not a well-studied topic although recovery is physiologically demanding. This experiment was conducted to determine the effectiveness of guided relaxation training over passive rest based on biochemical, mechanical and autonomic recovery measures.MethodsA total of 600 adolescent volleyball athletes (16.8 ± 1.1 years) were recruited across four training centres in China. Participants completed both relaxation and passive recovery conditions in a randomised crossover design, with a one-week washout between sessions. Blood lactate, muscle hardness (via Myoton), heart rate recovery at 60 s (HRR60s), total quality recovery (TQR), and soreness using a visual analogue scale (VAS) were measured at baseline, T1 (immediate post), T2 (15 min), and T3 (30 min). Nonparametric comparisons (Mann–Whitney U test) and an aligned rank transform analysis of variance (ANOVA) were used for between-group and within-group analyses, respectively.ResultsAt T3, mean lactate was significantly lower in the relaxation group (2.02 ± 0.72 mmol/L) than passive rest (2.76 ± 0.81 mmol/L; U = 34,011, p = 0.001). Muscle hardness reduction was greater in the relaxation group (−18.04 ± 7.12 N/m) compared to passive rest (−11.12 ± 6.87 N/m; U = 36,291, p = 0.002). HRR60s improved more markedly in the relaxation group (+31.84 ± 6.72 bpm vs. +26.91 ± 7.20 bpm; U = 33,712, p = 0.001). TQR scores were higher (15.9 ± 1.6 vs. 14.7 ± 1.9; U = 32,598, p = 0.001) and VAS soreness lower (2.4 ± 1.2 vs. 3.1 ± 1.4; U = 35,811, p = 0.001) under relaxation.ConclusionRelaxation training enhances multidimensional recovery outcomes in competitive volleyball athletes.